Intracellular localisation of proteins to specific cellular areas by nanocapsule mediated delivery. (14th September 2017) - Wang, Huabin; Chen, Ligang; Sun, Xianchao; Fu, Ailing
Abstract: Nanocapsules are promising carriers with great potential for intracellular protein transport. Although many studies have intended to improve cell uptake efficacy, there is an increasing interest in understanding of subcellular distribution of cargoes inside cells, which is essential for purposeful delivery of biomolecules into specific sites within cells. Herein, we interrogate the intracellular localisation of exogenous proteins, including fluorescein isothiocyanate (FITC)-labelled bovine serum albumin (BSA) and green fluorescent protein (GFP), mediated by specially designed nanocapsules. The results show that the designed nanocapsules can deliver the two types of fluorescent proteins into different cellular destinations (cytosol, nucleus or the whole cell), depending on the composition of nanocapsules. Meanwhile, several impact factors that influence the distribution of proteins in cells have also been investigated, and the results suggest that the localisation of capsule-mediated proteins in cells is strongly affected by the surface properties of nanocapsules, the types of stabilisers and proteins, and environmental temperatures. The rational control of intracellular localised delivery of exogenous proteins as we demonstrated in this study might open new avenues to obtain desired magnitude of drug effects for modulating cell activity.